Chapter Promuovere le competenze imprenditive degli studenti universitari: il caso dei Contamination Labs - Gamberi , Letizia (Studies on Adult Learning and Education, 2022)
The historical phase we are living, which is characterized by change management and the continuous redefinition of skills (Fiore et al. 2021), invites the university to question itself on the central role it plays for the formation of current and future. The work of the European Commission to address the improvement and adaptation of the skills of European citizens provides clear guidelines on which Higher Education is also called to commit. Among them, this paper focuses on the development of entrepreneurial skills, i.e. the ability to act on opportunities and ideas and to transform them into value for others. The Commission calls for the development of these competences at all levels of education, giving rise to entrepreneurial education training offers (Lackéus 2015). For this reason, and in order to respond to this need, since 2013 the Italian Ministry of University has established the Contamination Labs, places of contamination between students, teachers and local stakeholders aimed at developing interdisciplinary entrepreneurial education, which is also the subject of this research.